The Influence of Sales Promotion, Brand Trust and Lifestyle on Purchasing Decisions Against Purchasing Decisions at the Gatot Subroto Starbucks Store - ALIM BAHRI AZHARI; Erinchan Eduard Kalputra (TALENTA Publisher, Universitas Sumatera Utara, 2025)
This research aims to determine and analyze the influence of sales promotion, brand trust and lifestyle on purchasing decisions at Starbucks Gatot Subroto outlets, Medan City. This research is quantitative descriptive research with an associative approach method and the type of data used is primary data. The data analysis method used is multiple linear regression and assistance from SPSS. The population in this study was Starbucks Gatot Subroto consumers with a sample of 91 people. The results of this research show that partially, the variables sales promotion, brand trust, and lifestyle have a positive and significant effect on purchasing decisions at the Gatot Subroto Medan Starbucks Store. The simultaneous significance test shows that the sales promotion, brand trust and lifestyle variables together have a positive and significant effect on purchasing decisions at the Gatot Subroto Starbucks outlet in Medan City.